Qur’anic Ethical Paradigms and the Reconstruction of Moral Consciousness in the Modern Age - Muhammed Farhan K Kakkattiri (Penerbit Hellow Pustaka, 2026)
In a time marked by widespread geopolitical instability, global humanitarian crises, and shared emotional exhaustion, the Qur’an still offers deep moral and psychological insights into fostering hope (rajāʾ) and resilience (ṣabr). This paper explores how Qur’anic teachings, rooted in faith (tawakkul) and compassion (raḥmah), create a spiritual framework for facing challenges with moral strength and transformative endurance. Through theological reflection and analysis of key Qur’anic stories, especially those of the Prophetsprophets Yusuf (Joseph), Musa (Moses), and Muhammad (peace be upon him), the study shows how divine trials act as triggers for ethical growth, emotional renewal,and prophetsrenewal, andspiritual upliftment. In response to ongoing humanitarian issues like the crisis in Gaza, this paper connects the Qur’an’s guidance to a modern ethical view that links patience and perseverance with justice (ʿadl) and social responsibility. It argues that the Qur’an sees suffering not as divine punishment but as a chance for self-reflection, spiritual growth, and community support. By combining Qur’anic interpretation with modern views on psychological resilience and trauma recovery, the study illustrates how Qur’anic ethics can guide faith-based responses to global crises, restoring meaning, empathy, and inner balance in a troubled world. Ultimately, the paper emphasizes the Qur’an’s lasting message to confront despair with faith, injustice with compassion, and uncertainty with strong hope—positioning Islamic spirituality as both a moral guide and a source of psychological resilience today.